Bullying Victimization in High School: Perceptions and Responses of Black Parents. Issue 2 (24th February 2023) - Threlfall, Jennifer; Auslander, Wendy
Abstract: Youth who are bullied are more likely to experience negative social and educational outcomes; these problems may be exacerbated for Black youth who also experience racial bullying or discrimination as part of their victimization. This study investigated the ways in which Black parents understand and respond to their adolescent children's bullying victimization in school. Twenty-four parents of high school–aged children participated in qualitative interviews. Following a thematic analysis, results indicated three major ways in which parents responded to their children's victimization. Parents listened to their children and offered advice about how to respond to bullies. They engaged with their children's schools, identifying issues that perpetuated victimization. Last, they sought to draw lessons for their children about coping with victimization in the future. Findings highlighted how parents understand bullying to be influenced by institutional and societal factors, including racism and discrimination, and adapt their parenting strategies in response to the environment they expect their children to encounter.